2015
DOI: 10.1007/s40618-015-0405-5
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of CASR gene increase the risk of primary hyperparathyroidism

Abstract: Our results indicate that SNPs of CASR gene A986S (rs1081725) and R990G (rs1042636) may increase the risk of PHPT, and the polymorphisms can potentially be used as important biological markers for early diagnosis of PHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Studies have reported polymorphism in CaSR gene variants rs1801725, and rs1042636 are associated with various diseases, i.e., renal stone disease [10,14,20], prostate cancer [21], colorectal cancer [22], and primary HPT [23]. In our study, we have observed that individuals carrying GG genotype (rs1801725) and AA genotype (rs1042636) are associated with a high risk of developing renal stone disease.…”
Section: Discussionsupporting
confidence: 49%
“…Studies have reported polymorphism in CaSR gene variants rs1801725, and rs1042636 are associated with various diseases, i.e., renal stone disease [10,14,20], prostate cancer [21], colorectal cancer [22], and primary HPT [23]. In our study, we have observed that individuals carrying GG genotype (rs1801725) and AA genotype (rs1042636) are associated with a high risk of developing renal stone disease.…”
Section: Discussionsupporting
confidence: 49%
“…However, a dozen cases of parathyroid adenomas associated with CASR mutations have been reported, with two families having adenoma and/or familial hyperplasia of the parathyroids with papillary microcarcinoma [7–14]. Moreover, the R990G variant of CaSR seems to be more common in the general Chinese population, but also in Chinese patients with hyperparathyroidism [15].…”
Section: Genetic Causesmentioning
confidence: 99%
“…(164) Role of the CaSR polymorphisms in common forms of PHPT In line with the identification of CASR mutations causing PHPT disorders with a clear Mendelian mode of inheritance, as described in previous section, common CASR single nucleotide polymorphisms (SNPs) may also influence the phenotype of PHPT, as they have been associated by genomewide association studies (GWASs) with circulating calcium and PTH concentrations in general outbred populations. (165,166) No GWASs have been performed on PHPT to date, but findings from previous association studies of limited sample size (167)(168)(169) are in line with the contention that CASR constitutes a strong candidate gene influencing the pathogenesis of more common forms of PHPT arising in the general population. Somatic CASR mutations have not been detected in parathyroid tumors from PHPT patients, (170)(171)(172)(173) and are therefore unlikely to influence their pathogenesis.…”
Section: Fhh and Phpt Caused By Germline Mutations Of The Casr And Pa...mentioning
confidence: 75%